Sexual abuse leading to secondary syphilis in an intellectually disabled person: a case report - Munusamy, Rajesh; Nagaraja, Nithin (International Journal of Research in Dermatology, 2021)
Syphilis is a sexual transmitted infection (STI) caused by a spirochete, Treponema pallidum. Condylomata lata is a characteristic lesion seen in secondary syphilis. Here we reported a case of 24 year old unmarried male with intellectual disability who presented with condyloma lata over the scrotum, prepuce and perianal region and with moth eaten alopecia over scalp since 1 month. Here the patients mother revealed he had promiscuous relationship with multiple friends, which is a sexual abuse since the patient is intellectually disabled. Clinically diagnosed as secondary syphilis. Venereal disease research laboratory (VDRL) test titre was reactive at 1:32 and Treponema pallidum hemagglutination test (TPHA) was positive. Biopsy was also done, which confirmed diagnosis. Single dose of injection benzathine penicillin G, 2.4 million units was administered intramuscularly. Patient did not develop a Jarisch-herxheimer reaction. On follow up his lesions healed and VDRL titres also came down and non-reactive at 3 months. Here in this case sexual abuse lead to secondary syphilis since patient was intellectually disabled so he couldn’t address his complaints clearly. Hence counselling was done to the patient and family members by dermatologist and psychiatrist.